2013
DOI: 10.1002/lary.23854
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and therapeutic response of objective tinnitus due to middle ear myoclonus: A large case series

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 11 publications
1
39
0
5
Order By: Relevance
“…Tinnitus secondary to middle ear myoclonus is very rare, and consequently there are very few reports of it in the English literature [8][9][10][11][12]. It has been suggested that the crackling or buzzing sounds reported are caused by repetitive and abnormal tensor tympani and stapedial muscles contractions [11].…”
Section: ) Etiologymentioning
confidence: 99%
See 4 more Smart Citations
“…Tinnitus secondary to middle ear myoclonus is very rare, and consequently there are very few reports of it in the English literature [8][9][10][11][12]. It has been suggested that the crackling or buzzing sounds reported are caused by repetitive and abnormal tensor tympani and stapedial muscles contractions [11].…”
Section: ) Etiologymentioning
confidence: 99%
“…These myoclonic movements are thought to be a form of segmental myoclonus involving brainstem innervated muscles. Vascular, infectious and demyelinating disorders as well as anxiety, trauma and neoplastic disease have all been implicated in the etiology of segmental myoclonus [9,11,12]. In a previous report of the largest case series of middle ear myoclonus, 58 enrolled patients had a mean age of 29.8 years (range, 6-70 years) and 20.7% (n=12) were less than 10 years old [12].…”
Section: ) Etiologymentioning
confidence: 99%
See 3 more Smart Citations